A conceptual framework of the low cost carrier - airport relationship development in Southeast Asia / Eliver Lin ...[et al.] - Lin, Eliver; Mak, Barry; Wong, Kevin (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2009)
The purpose of this study is to explore the relationship development between Low Cost Carriers (LCCs) and airports in Southeast Asia. LCCs are growing rapidly in Southeast Asia and their development inevitably involves establishing relationships with airports. As LCCs continue this impressive growth rate in the future, it is not difficult to foresee that there will be more and more relationships establish between LCCs and airports which make it a valuable topic to be studied. International air service is one of the major characteristics of LCCs in Southeast Asia. Traditionally, international airlines and airport relationships have been confined to bilateral air service agreement (BASA). Besides, that most of the airlines are national carriers while most of the airports are government owned and controlled in Southeast Asia. Therefore the traditional airlines-airport relationship in Southeast Asia is between two governments' organizations and confined to BASA. However, most of the the LCCs in Southeast Asia are privately owned commercial organization. Therefore the LCC-airport relationship is between a commercial and a government organization. As a result, the knowledge of the traditional airlines-airport relationship cannot be applied to the LCC-airport relationship. However, the issue of the LCC-airport relationship development has seldom been addressed by previous researchers. This study aims at filling this research gap. This study will borrow the idea of the Interaction Model (IMP Group, 1982), power imbalance, mutual dependence (Pfeffer and Salancik, 2003) and mutuality (Ford, Hakansson & Johanson, 1986) to explore and explain the LCC-airport relationship in Southeast Asia. This research will first study what factors lead a LCC and an airport to start up a relationship, and how these factors affect their relationship development. Whether and how power, dependence and mutuality will affect their relationship will also be studied.